The awareness of the Solo Parent's Welfare Act of 2000 among selected working single mothers in Metro Manila - Miaral, Anne Cristine O.
The Constitution of the Philippines recognizes the importance of the family. This includes solo parent families. Republic Act 8972 or the "Solo Parents' Welfare Act of 2000," enunciated the policy of the State to promote the family as the foundation of the nation and as such, developed a program of services for the benefit of single parents. Thus, this researcher was prompted to conduct a study on the awareness of selected working single mothers of RA 8972 and the factors that facilitate the impede its implementation in the workplace. The Review of related Literature discusses the following: (1) the definition of the solo parent; (2) the different types of solo parents; (3) the problems they face; (4) the support granted by the government by presenting the law's legislative history, its components, and benefits; (4) the awareness of RA 8972; and (5) the factors that facilitate and impede its implementation. This study is qualitative in nature. An exploratory descriptive approach was used since this is the initial study involving a Solo Parent Law. The respondents are 30 solo mother, as defined in RA 8972, aged 21 to 60 years old. Out of the 30 respondents, 14 fall below the poverty income bracket, as such is entitled to the complete benefits of the law. As a tool for data gathering, the researcher used a questionnaire which was classified based on the objectives of the study. Based on the data gathered, solo parents are not aware of RA 8972. When asked whether they have heard of such law, most of them remarked in the negative. The factors that impede its implementation are: the lack of awareness by the solo parent and the community, the failure of the government to monitor its implementation and the limitation provided by the law which grants complete benefits only to those single parents under the poverty threshold. As an initial study, the author opted to analyze a small sample only, but for extensive researches it would be wise to study a larger sample to verify the previous findings. Another recommendation is the creation of an information dissemination program to increase the awareness of the said law by tapping the media, influential, solo parent personalities, NGO's and other organizations. More importantly, there is a need to look into the amendment of Section 4 RA 8972, which limits the grant of the benefits to only those solo parents falling below the poverty line.